Social Capital in Shaping the Predecessors of Entrepreneurial Intentions - Gaweł, Aleksandra; Pietrzykowski, Maciej (Studia Oeconomica Posnaniensia, 2019)
The purpose of the article is to determine the impact of social capital on shaping the predecessors of entrepreneurial intention in accordance with Ajzen’s theory of planned behaviour, i.e. an attitude towards entrepreneurial behaviour, subjective norms and perceived control of behaviour. Conducting a survey among students, it was assumed that the assessment of the professional career of the mother, father and own may be measures of social capital, because perceiving the professional success of the relatives gives the conviction about the possibilities of access to the network of business connections and substantive, financial or emotional support. The research results show that the assessment of one’s own career influences the perceived control of the situation during the entrepreneurial process. A father’s career assessment sets a certain standard, which forms the basis for shaping subjective norms of entrepreneurial behaviour. On the other hand, the attitude towards entrepreneurial behaviour is the result of an assessment of one’s own career and a father’s career. Thus, the control of behaviour depends on individual factors, subjective norms are shaped by the environment, and the attitude towards behaviour is the resultant of individual and external factors. The assessment of a maternal career turned out to be statistically insignificant.